Plitidepsin in adult patients with COVID-19 requiring hospital admission: A long-term follow-up analysis - Varona, Jose F.; Landete, Pedro; Paredes, Roger; Vates, Roberto; Torralba, Miguel; Guisado-Vasco, Pablo; Porras, Lourdes; Muñoz, Patricia; Gijon, Paloma; Ancochea, Julio; Saiz, Elena; Meira, Fernanda; et al. (Frontiers in Cellular and Infection Microbiology, 2023)
The APLICOV-PC study assessed the safety and preliminary efficacy of plitidepsin in hospitalized adult patients with COVID-19. In this follow-up study (E-APLICOV), the incidence of post-COVID-19 morbidity was evaluated and any long-term complications were characterized. Between January 18 and March 16, 2022, 34 of the 45 adult patients who received therapy with plitidepsin in the APLICOV-PC study were enrolled in E-APLICOV (median time from plitidepsin first dose to E-APLICOV enrollment, 16.8 months [range, 15.2–19.5 months]). All patients were functionally autonomous with regard to daily living (Barthel index: 100) and had normal physical and neurological examinations. From the APLICOV-PC date of discharge to the date of the extension visit, neither Common Terminology Criteria for Adverse Events version 5.0 (CTCAE v5) grade 3-4 complications nor QT prolongation or significant electrocardiogram (EKG) abnormalities were reported. Five (14.7%) patients had another COVID-19 episode after initial discharge from APLICOV-PC, and in 2 patients (5.9%), previously unreported chest X-ray findings were documented. Spirometry and lung-diffusion tests were normal in 29 (85.3%) and 27 (79.4%) patients, respectively, and 3 patients needed additional oxygen supplementation after initial hospital discharge. None of these patients required subsequent hospital readmission for disease-related complications. In conclusion, plitidepsin has demonstrated a favorable long-term safety profile in adult patients hospitalized for COVID-19. With the constraints of a low sample size and a lack of control, the rate of post-COVID-19 complications after treatment with plitidepsin is below the average prevalence from recent meta-analysis. (ClinicalTrials.gov Identifier: NCT05121740; https://clinicaltrials.gov/ct2/show/NCT05121740)